Factors influencing the number of non-timber forest product species used at the individual, household and village levels in Vhembe, Limpopo Province, South Africa - Mulaudzi, Takalani Rachel (Rhodes University, Faculty of Science, Department of Environmental Science)
Non-Timber Forest Products (NTFPs) are wild biological resources obtained from natural landscapes, agricultural systems, and rural and urban regions for a variety of uses. NTFPs contribute significantly to livelihoods and living standards by offering a variety of socioeconomic benefits such as food, health, income generation, and safety nets. These multiple benefits are provided by a wide diversity of plant, animal and fungal species in different settings. However, the precise number of NTFP species used depends on the scale of assessment, namely use by individuals, by households and by villages. Consequently, it is difficult to compare numbers of species used between studies because of the differing scales. As a result, the objective of this study was to determine the number of NTFP species used at three different scales and how each is correlated with appropriate scale-dependent contextual variables. This objective was met by sampling individuals and whole households in five villages in the Vhembe District in Limpopo Province, South Africa. Twenty households were randomly selected in each village, providing a total sample of 100 households and 179 individuals in those households. In each household, every adult member was interviewed individually about the NTFPs that they used or knew. The major questions covered the NTFP species used, the respondents' socioeconomic level, the NTFP species used previously, and if the number of NTFP species are changing in the landscape. Data were reported per individual as well as per household and per village. The household level was derived by adding the responses of all the adults in each household but excluding duplicates. The same approach was used at the village scale, namely, the data across the 20 households were pooled, and duplicates were omitted. Patterns of NTFP use were examined by type of NTFP, and analysis using standard statistical tests, along with a Principal Components Analysis and a multivariate Detrended Correspondence Analysis of the NTFP species composition across villages. A total of 275 species of NTFPs were mentioned across the entire sample, including 81 species of firewood, 48 species of edible insects, 43 species of wild vegetables, 40 species of edible fruits, 38 species of wood utensils, 28 species of medicinal plants, 23 species of thatch grass, 19 species of poles, 19 species of wood for carvings, nine species of reeds, eight species of mushroom, and eight species of fodder. Of these species, some species had more than one use. Approximately 90% of the species used by the respondents were native species. Wild vegetables (e.g., Corchorus olitorius, Amaranthus capensis, Bidens pilosa), firewood (e.g., Colophospermum mopane, Parinari curatellifolia, Combretum hereroense), wild fruit (e.g., Landolphia kirkii, Vangueria infausta), and edible insects (e.g., Imbrasia belina, Macrotermes michaelseni, Encosternum delegorguei) were the most often used NTFPs by communities in the Vhembe area. Most of the households relied on NTFPs for subsistence. At the scale of an individual, the mean number of NTFP species used was 26.8Â±12.6 across the five villages. When considering a household, the mean number was 36.1Â±10.7 species. When aggregated across the 20 households per village, the mean number per village was 105.2Â±34.1 species. The species accumulation curve showed that 20 households per village were reasonably representative for four of the five villages. The results from the principal component analysis (PCA) and correlation analysis revealed that age, education, and employment status were significantly associated with the number of species used by individuals, whereas gender showed no clear correlation. At the household scale, household size was positively related with the number of species used, but income level and income source were not. At the village scale, attributes such as proximity to a town, settlement type, vegetation type, and distance to a nearby savanna all had some influence on the number of NTFP species listed. Most of the respondents felt that the number of species used had increased over the last 10"“15 years, although some stated the opposite. Increases were attributed by traditional councils bans, the establishment of protected areas, and restoration. Activities eroding the number of NTFP species were identified as clear felling for farming, climate change, and over-harvesting. This study suggests that communities must be made more aware of the overharvesting of NTFP species in the savanna to avoid biodiversity loss.
Keywords: Non-timber forest products -- South Africa Vhembe District Municipality; Household ecology; Principal components analysis; Detrended Correspondence Analysis